Domestic Violence, Employment and Divorce - Audra J. Bowlus; Shannon N. Seitz (Queen's University, Department of Economics, 2002)
Using unique, representative data on domestic violence, we document several stylized facts on abuse: the average characteristics of abused wives and abusive husbands are markedly different than the characteristics of individuals in non-violent marriages, the vast majority of violent marriages end in divorce, and employment rates are lower for women who experience abuse. We then construct a sequential model of employment, marriage and abuse. The results indicate abuse is the primary factor in the decision to divorce and witnessing violence as a child is a strong predictor of becoming an abusive spouse. Policy experiments suggest men are more responsive to policies designed to increase the costs of abuse than women are to policies reducing the cost of leaving violent marriages and policies designed to reduce the inter-generational effects of domestic violence may be promising strategies for preventing abuse.
Keywords: O10; J20; J12; 330; Domestic Violence; Abuse; Employment; Marriage; Divorce; Frauen; Gewalt; Weibliche Arbeitskräfte; Theorie; Ehe